1968
DOI: 10.1017/s001675680005247x
|View full text |Cite
|
Sign up to set email alerts
|

The main features of the tectonic structure of Spitsbergen

Abstract: The Spitsbergen archipelago is situated in the north-westernmost part of the Barents Shelf. The structural position of the archipelago and the variety of its geological complexes make this region very important for understanding the tectonic history of the Atlantic sector of the Arctic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…The existence of the last shield has been proposed by Sokolov e t al. [5] and it extends froni Spitsbergen t o Franz Joseph Land. Its existence is, however, not well established.…”
Section: Geological Frameworkmentioning
confidence: 97%
“…The existence of the last shield has been proposed by Sokolov e t al. [5] and it extends froni Spitsbergen t o Franz Joseph Land. Its existence is, however, not well established.…”
Section: Geological Frameworkmentioning
confidence: 97%
“…However, Nathorst (in Suess, 1888) perhaps first drew this boundary between western 'Archaean' rocks and eastern 'Hecla Hoek', a view that persisted at least until Tyrrell (1922) and long afterwards in Soviet publications (e.g. Sokolov, Krasil'shchikov & Livshits, 1968), and now revived by Manby (1990).…”
Section: B the Relationship Between The Stubendorffbreen And Lomfjmentioning
confidence: 99%
“…Harland 1961Harland , 1965Harland , 1969Sokolov, Krasiltchikov & Livshitz 1968;Kellogg 1975;Faleide, Gudlaugsson & Jacquart 1984). Two events dominate that history and both are related to the movement of Greenland along the western edge of the Barents shelf.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Harland et al (1974) suggested that at least 200 km, and as much as loo0 km, of transcurrent displacement may have been accomodated by the Billifjorden Fault Zone, or have been distributed among two or more faults, at that time. The major faults, along which motion occurred, run predominatly N-S and form the boundaries of the main structural elements of the archipelago (Sokolov et al 1968). Harland (1979) points out, however, that these faults are seldom observed directly because they pass through zones of poor exposure, or are covered by surficial deposits, ice, or water.…”
Section: Tectonic Settingmentioning
confidence: 99%